Confirmation of the cardiac safety of nolasiban in a randomised cohort of healthy female volunteers - Täubel, Jörg (Sci Rep, 2021)
Nolasiban is an orally active oxytocin receptor antagonist being developed to increase the efficiency of assisted reproductive technologies. This study evaluated the pharmacokinetics, pharmacodynamics, and cardiac safety of nolasiban in 45 healthy women of child-bearing age. Nolasiban was administered in a fasted state with a standardised lunch served 4.5 h post-dose. Concentration-effect modelling was used to assess the effect of two dosages of nolasiban (900 mg and 1800 mg) on QTc following single-dose administration. We found no significant change in QTc at all tested dosages. Two-sided 90% confidence intervals of geometric mean C(max) for estimated QTc effects of nolasiban were below the threshold of regulatory concern. The sensitivity of the assay to detect small changes in QTc was confirmed by a significant shortening of QTc between 2 and 4 h after consumption of a meal, which served to validate the model. Independent of the nolasiban assessment, this study also explored the effects of sex hormones on ECG parameters, especially QT subintervals. We found a significant relationship between JTpc and oestradiol. Heart rate was negatively correlated with progesterone. This study confirms the cardiovascular safety of nolasiban and describes relationships of sex hormones and ECG parameters.